Utilizing expired duloxetine as an eco-friendly corrosion inhibitor for API 5L X52 carbon steel in aqueous solutions: Experimental and computational analysis - Seham H. Bashir; Mariem M. Motawea; Ayman A.O. Younes; Amira A.E. Satti; Rabeea M.A. Daoub; Mohamed F. Atia (Results in Chemistry)
The inhibiting influence of expired duloxetine drug (EDD) toward corrosion performance of API 5L X52 carbon steel (X52-CS) in 1.0 M HCl was planned to utilize weight loss (Wl), potentiodynamic polarization (PDP), AC impedance spectroscopy (EIS), Density Functional Theory (DFT), Monte Carlo simulations (MC) and surface morphology. The hindrance efficiency of EDD improved by raising both doses of the drug and temperature. EDD has good properties for the corrosion inhibition of API 5L X52 carbon steel (X52-CS) in 1 M HCl solution. 91.3 % efficiency was achieved at the 300 ppm concentration of EDD. However, inhibition efficiency increased with rising temperatures, increase from 91.3 % at 298 K to 93.4 % at 328 K (all at 300 ppm). The parameters obtained from thermodynamics due to corrosion and adsorption procedures have been measured and debated. The adsorption of EDD on the X52-CS surface in HCl has gotten to follow isotherm Langmuir. EDD has adsorbed a mixed (physical and chemical) with the predominance of chemisorption on X52-CS surface. The inhibitor (EDD) may be classified as an anodic, cathodic, or mixed-type inhibitor on the basis of PDP tests. EIS data demonstrated that the charge-transfer resistance (Rct) increases while the capacitance of the double layer (Cdl) decreases as EDD concentration increases, thereby further substantiating the proposed adsorption process mechanism. The surface tests of protected X52-CS were examined by scanning electron microscope (SEM), atomic force microscopy (AFM), and foruire transform infra-red (FT-IR). DFT calculations and MC simulations provided further insight into the chemical interactions between EDD and the X52-CS surface. The novel application of EDD is shown in this study, highlighting its affordability and non-toxicity, which make it a viable substitute for corrosion control in manufacturing environments.